2016
DOI: 10.1590/2177-6709.21.3.067-072.oar
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Psychosocial Impact of Dental Aesthetics Questionnaire for use on Brazilian adolescents

Abstract: Introduction:The Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ) is a multi-item psychometric instrument used to assess patients' perspective of the impact specifically related to Orthodontics. The cross-culturally adapted Brazilian version of the PIDAQ has demonstrated good reliability, validity and acceptability.Objective: The aim of the present study was to test the validity and reliability of the Brazilian version of the PIDAQ for use among adolescents aged between 11 and 14 years old.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 24 publications
(35 reference statements)
1
18
0
1
Order By: Relevance
“…Similar to our PIDAQ(A), two other related studies have found that the questionnaire comprised three factors [43,44], while one study yielded only two factors [17], and another study yielded five factors [47]. In addition, there are a small number of adaptations which did not incorporate factor analysis into their validation [48][49][50].…”
Section: Discussionmentioning
confidence: 72%
“…Similar to our PIDAQ(A), two other related studies have found that the questionnaire comprised three factors [43,44], while one study yielded only two factors [17], and another study yielded five factors [47]. In addition, there are a small number of adaptations which did not incorporate factor analysis into their validation [48][49][50].…”
Section: Discussionmentioning
confidence: 72%
“…Two translations have found that the instrument has three dimensions [17,23], and one translation revealed five dimensions [15]. Finally, there are a few translations which have not included factor analysis in their validation [13,16,25]. It can be concluded that PIDAQ seems to display different factor structures in different translations and populations.…”
Section: Discussionmentioning
confidence: 98%
“…PIDAQ has been translated into several languages and validated for use on adult populations [13][14][15][16][17][18][19][20][21]. The original adult version of PIDAQ has also been translated and validated on children and adolescents [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Este questionário desenvolvido por Slade e Spence (1994) foi posteriormente atualizado, em 1997, e uma versão simplificada foi criada, o OHIP-14 que tem sido comumente empregado em estudos recentes, por ter uma sólida base conceitual, boas propriedades psicométricas conhecida e fácil administração 29 . Apenas em um estudo, verificou-se a aplicação de um instrumento com abordagem especifica para uma condição de saúde bucal (Ortodontia) objetivando avaliar o impacto psicossocial nestes adolescentes 19 .…”
Section: Discussionunclassified